Feeding aquaculture growth through globalization: Exploitation of marine ecosystems for fishmeal - Lisa Deutsch (2018)
Like other animal production systems, aquaculture has developed into a highly globalized trade-dependent industry. A major part of aquaculture technology requires fishmeal to produce the feed for farmed species. By tracing and mapping patterns of trade flows globally for fishmeal we show the aquaculture industry's increasing use of marine ecosystems worldwide. We provide an in-depth analysis of the growth decades (1980-2000) of salmon farming in Norway and shrimp farming in Thailand. Both countries, initially net exporters of fishmeal, increased the number of import source nations of fishmeal, peaking in the mid-1990s. Thailand started locally and expanded into sources from all over the globe, including stocks from the North Sea through imports from Denmark, while Norway predominantly relied on northern region source nations to feed farmed salmon. In 2000, both have two geographically alternate sources of fishmeal supply: the combination of Chile and Peru in South America, and a regional complement. We find that fishmeal trade for aquaculture is not an issue of using ecosystems of the South for production in the North, but of trade between nations with industrialized fisheries linked to productive marine ecosystems. We discuss the expansion of marine ecosystem appropriation for the global aquaculture industry and observed shifts in the trade of fishmeal between marine areas over time. Globalization, through information technology and transport systems, has made it possible to rapidly switch between marine areas for fishmeal supply in economically connected food producing systems. But the stretching of the production chain from local to global and the ability to switch between marine areas worldwide seem to undermine the industry's incentives to respond to changes in the capacity of ecosystems to supply fish. For example, trade information does not reveal the species of fish that the fishmeal is made of much less its origins and there is lack of feedback between economic performance and impacts on marine ecosystem services. Responding to environmental feedback is essential to avoid the trap of mining the marine resources on which the aquaculture industry depends. There are grounds to suggest the need for some global rules and institutions that create incentives for seafood markets to account for ecosystem support and capacity. © 2006 Elsevier Ltd. All rights reserved.